Dialektika Legalitas Hak Asasi Manusia dan Rasionalisme Moral - Leatemia, Philip Josep (Jurnal Hukum Caraka Justitia, 2021)
Human rights are basic rights or basic rights that humans are born with as a gift from God Almighty. These human rights form the basis of other rights and obligations. As is known, in addition to human rights, there are human rights that in our social life should receive attention first in their implementation. We must fulfill our obligations first, then demand rights.In an individualistic society, there is a tendency for excessive prosecution of the implementation of these human rights, even though the implementation of human rights cannot be demanded absolute implementation because the prosecution of the absolute implementation of human rights means violating the same human rights of other people. For example, print and television news reporters often use argumentation in finding or interviewing artists who have personal problems, these reporters dig and interview artists down to the most personal issues in the artist's life, and if the artist refuses or is angry, the answer is the journalist is carrying out his journalistic duties and they demand that their human rights be fulfilled or obeyed so that the artist must tell his problem.Here it can be seen that on the journalist's side, he demands that his human rights be fulfilled, on the other hand, it can be seen that the artist's human rights are trampled on by the journalists, which means that the artist's human rights are being violated by the journalists. The question is: Where is the legality of human rights and moral rationalism?